Bernard Magubane's critique of anthropology in southern Africa: an introductory essay. Issue 2 (3rd July 2019) - Nyoka, Bongani
ABSTRACT: This essay is an attempt to piece together the fundamentals of Bernard Magubane's critique of anthropology in southern Africa. The point is not to berate the discipline of anthropology, but to discuss Magubane's work in relation to it. The essay comprises three main parts. First, it examines Magubane's critique of southern African anthropology in a colonial situation – particularly in the 1960s, 1970s and 1980s. Second, it assesses the usefulness of anthropological notions of pluralism and 'tribalism' in explaining conflicts in Africa. The remainder of the essay contends with anthropological themes such as social change and 'modernisation' in southern Africa. Generally, anthropology had problems at two levels: political and epistemological. Politically, anthropology was a handmaiden of colonialism and imperialism; and its main flaw was to study southern African societies outside of history and context. Epistemologically, anthropology is a discipline founded on alterity, that is, on studying the cultural Other.